A touch of Steele - Maxwell, Cathy (Maxwell, Cathy. Gambler's daughters novel., 2025)
"From the moment the enigmatic Mr. Steele 'almost' kissed her on a Dublin street, her world was forever altered. He commands the respect of rogues and nobles alike--and Gwendolyn owes him a favor. She believes he owes her a kiss. Beckett is a lone wolf. However, he needs Gwendolyn to discover the secrets of his past. He has no choice but to seek her help--even though she threatens the walls he has carefully erected around his heart. He doesn't need a woman in his life;she knows he can't live without her. Together, they must navigate aworld of deception, where love defies the odds and secrets threatento unravel everything they hold dear. Will they find a future together, or will the past tear them apart?"--